The impact of parental social support, coach-athlete interaction, training partners, and competitive experience on mental toughness in junior tennis players - Issadam Khusni; Abdul Alim; Ismail Gani; Tito Pangesti Adji; Jeff Agung Perdana (JURNAL SPIRITS, 2026)
This study aims to analyze the influence of parental social support, coach interaction, training partners, and competitive experience on the mental toughness of national junior tennis athletes. This research employs a quantitative approach. The study was conducted during the National Junior Tennis Championship “DETEC K3N7O3N9 OPEN 2025” at Gelora Merdeka Tennis Court, Sukoharjo, Central Java. The sample consisted of 227 national junior tennis athletes participating in the championship. Data were collected using questionnaires. Data analysis involved regression analysis following a series of assumption tests. The results indicate that: (1) Parental social support, coach interaction, training partners, and competitive experience simultaneously have a significant positive effect on mental toughness, with a significance value (p-value) of 0.000; (2) Partially, the training partner variable does not significantly influence mental toughness, as evidenced by a significance value of 0.198.